2012
DOI: 10.1089/gtmb.2011.0183
|View full text |Cite
|
Sign up to set email alerts
|

HLA B27 Subtype Distribution Among Patients with Ankylosing Spondylitis in Eastern Turkey

Abstract: Human leukocyte antigen (HLA) B27 has a strong association with ankylosing spondylitis (AS) and other spondyloarthropathies. More than 70 subtypes of HLA B27 have been described. The present study investigated B27 subtype distribution among B27-positive patients with AS classified according to the modified New York criteria and healthy controls. Sequence-specific primer polymerase chain reaction technique was used for B27 subtyping of 43 unrelated patients with AS and 39 volunteer bone marrow donors. Among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…12 In Iran and Turkey, HLA-B*27:02 and HLA-B*27:05 are common AS associated alleles. 6,13 HLA-B*27:07 was found as the predominant allele in AS patients in current study, followed by HLA-B*27:03 and HLA-B*27:05. These findings are supported by other studies conducted globally.…”
Section: Discussionsupporting
confidence: 47%
“…12 In Iran and Turkey, HLA-B*27:02 and HLA-B*27:05 are common AS associated alleles. 6,13 HLA-B*27:07 was found as the predominant allele in AS patients in current study, followed by HLA-B*27:03 and HLA-B*27:05. These findings are supported by other studies conducted globally.…”
Section: Discussionsupporting
confidence: 47%
“…A study of HLA-B27 Subtypes in Iranian patients with Ankylosing Spondylitis detected two subtypes, B*2705 (63.4%) and B*2702 (36.6%) [31]. Meanwhile, B*2746, B*2749, B*2767, B*2702 and B*2705 subtypes were detected among Ankylosing Spondylitis patients in Turkey [32]. HLA-B27 was shown to have highest prevalence in ankylosing spondylitis and least prevalence in juvenile rheumatoid arthritis among Iranian population [33].…”
Section: Discussionmentioning
confidence: 99%
“…AS occurs most commonly in the 20s age group, and males are more susceptible 2 . Genetic factors are thought to be related to AS 3‐8 . It has been reported that more than 90% of AS patients carry the human leukocyte antigen (HLA)‐B27 gene 9 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Genetic factors are thought to be related to AS. [3][4][5][6][7][8] It has been reported that more than 90% of AS patients carry the human leukocyte antigen (HLA)-B27 gene. 9Enterobacteria infection, 10 such as with Klebsiella pneumoniae, Proteus mirabilis, Escherichia coli, was deemed in previous studies to be another risk factor causing AS.Among Enterobacteria, K. pneumoniae has received the most attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation